Cu removal and response mechanisms of periphytic biofilms in a tubular bioreactor. (January 2018) - Ma, Lan; Wang, Fengwu; Yu, Yuanchun; Liu, Junzhuo; Wu, Yonghong
Highlights: Periphyton is effective and sustainable in removing Cu from wastewater. Periphyton had a Cu removal efficiency of maximally 99%. Periphyton acclimated to Cu stress by regulating its microbial composition. Algae, Gammaproteobacteria and Bacteroidia were dominant in Cu removal. Abstract: This work studied Cu removal and response mechanisms of periphytic biofilms in a tubular bioreactor. Periphytic biofilms immobilized in a tubular bioreactor were used to remove Cu from wastewater with different Cu concentrations. Results showed that periphytic biofilms had a high removal efficiency (max. 99%) at a hydraulic retention time (HRT) of 12 h under initial Cu concentrations of 2.0 and 10.0 mg L −1 . Periphyton quickly adapted to Cu stress by regulating the community composition. Species richness, evenness and carbon metabolic diversity of the periphytic community increased when exposed to Cu. Diatoms, green algae, and bacteria ( Gammaproteobacteria and Bacteroidia ) were the dominant microorganisms and responsible for Cu removal. This study indicates that periphytic biofilms are promising in Cu removal from wastewater due to their strong adaptation capacity to Cu toxicity and also provides valuable information for understanding the relationships between microbial communities and heavy metal stress.